Monte Carlo modelling of pixel clusters in Timepix detectors using the MCNP code - Šolc, Jaroslav; Jakůbek, Jan; Marek, Lukáš; Oancea, Cristina; Pivec, Jiří; Šmoldasová, Jana; Tesař, Jiří; Vykydal, Zdeněk (Physica medica, 2022)
The track structure of the signal measured by the semiconductor pixel detector Timepix3 was modelled in the Monte Carlo MCNP® code. A detailed model at the pixel-level (256 × 256 pixels, 55 × 55 μm2 pixel size) was developed and used to generate and store clusters of adjacent hit pixels observed in the measured data because of particle energy deposition path, charge sharing, and drift processes. An analytical model of charge sharing effect and the detector energy resolution was applied to the simulated data. The method will help the user sort the measured clusters and distinguish radiation components of mixed fields by determining the response of Timepix3 detector to particular particle types, energies, and incidence angles that cannot be measured separately.